IMPACT OF IMPLEMENTING GREEN ROOF AND GREEN FACADE ON EXISTING BUILDINGS - Mohson, Zainab Hamid; Ismael, Zeyad Ali (NED University Journal of Research, 2025)
This paper examines the impact of greening technology on traditional buildings, addressing the lack of understanding regarding its effects. Results show that greening enhances thermal comfort by lowering humidity and temperature. Humidity fell from forty-five percent to twenty-seven percent and from forty-eight percent to thirty-three percent gradually after greening, while the temperature decreased from 32°C (90°F) to 24°C (75°F) and from 33°C (91°F) to 25°C (77°F). These changes highlight greening's potential as a long-term strategy to improve climate and comfort, offering a more comfortable atmosphere in hot and humid climates while also reducing energy loss, and improving the quality of life in these locations.